2018
DOI: 10.3390/ijms19103263
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Analysis of lncRNAs, miRNAs, and mRNA-Associated ceRNA Network in an Atopic Dermatitis Recurrence Model

Abstract: Atopic dermatitis (AD) is a prevalent inflammatory skin disease characterized by its chronic nature and relapse. Ample evidence suggests that non-coding RNAs play a major role in AD pathogenesis. However, the mechanism remains unknown, particularly in AD recurrence. Dynamic morphological and cytokine changes were measured throughout the whole course of an FITC-induced AD recurrence murine model. Microarray assay and integrative analysis were performed to comprehensively explore long non-coding RNA (lncRNA), me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 26 publications
(27 reference statements)
0
27
0
Order By: Relevance
“…Similar results were found in comparing skin and scalp psoriasis [134]. The phenotypically severe psoriasis form generalized psoriasis pustulosa (GPP) exhibited a strong granulocyte chemotactic transcriptome reflecting the disease's histological findings (e.g., subcorneal neutrophilic pustules and neutrophilic spongiosis) [135]. Marrakchi et al, presented the role of IL36RN mutation in a case of hereditary GPP and suggested a strong role of IL-1β and IL-36 in the disease pathophysiology [136].…”
Section: Disease Subgroupingmentioning
confidence: 54%
See 1 more Smart Citation
“…Similar results were found in comparing skin and scalp psoriasis [134]. The phenotypically severe psoriasis form generalized psoriasis pustulosa (GPP) exhibited a strong granulocyte chemotactic transcriptome reflecting the disease's histological findings (e.g., subcorneal neutrophilic pustules and neutrophilic spongiosis) [135]. Marrakchi et al, presented the role of IL36RN mutation in a case of hereditary GPP and suggested a strong role of IL-1β and IL-36 in the disease pathophysiology [136].…”
Section: Disease Subgroupingmentioning
confidence: 54%
“…Additionally, the IL-1R antagonist anakinra shows frequently incomplete treatment response and IL-36 may be a more promising druggable target. However, despite GPP-specific features and susceptibility factors (e.g., CARD14 and AP1S3) [135], IL17 mRNA is also constantly present in pustular lesions. In line with this, unsupervised clustering revealed an overlap between plaque psoriasis and GPP.…”
Section: Disease Subgroupingmentioning
confidence: 97%
“…There are multiple models of AD in the mouse, using various antigens such as fluorescein isothiocyanate (FITC) [32] and dinitrochlorobenzene (DNCB) [33]. These models rely on a sensitization period wherein the antigen is applied directly to the skin of the abdomen or flank to allow dendritic cells to process and present the antigen to reactive T cells, which clonally expand and produce Th2 and Th17 cytokines and chemokines.…”
Section: Introductionmentioning
confidence: 99%
“…The immune response can be gauged by measuring the ear thickness using calipers, and by isolating proteins from ear tissue homogenate to measure cytokine and chemokine levels. For example, the FITC model is characterized by elevated expression of IL-1β, IL-4, IL-5, IL-6, IL-13, IL-17, eotaxin, monocyte chemoattractant protein (MCP)-1/chemokine (C-C motif) ligand (CCL)-2, macrophage inflammatory protein (MIP)-1α/CCL4, RANTES (Regulated on Activation, Normal T Cell Expressed and Secreted), and thymus and activation-regulated chemokine (TARC) in the ear tissue [32]. AD therapeutics have been successfully tested in these models.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation